Effects of fibre impairments in variable weight optical code division multiple access system - Seyedzadeh, S.; Moghaddasi, M.; Anas, S.B.A. (Institution of Engineering and Technology (IET), 2016)
Variable weight optical code division multiple access system (VW-OCDMA) is developed to provide service differentiation in optical metro networks where different applications demand for different quality of services. In VW-OCDMA, different number of wavelengths carries the data for different services. Hence, the fibre impairment effects vary for different services. In this study, the performance of a VW-OCDMA is analysed under the impact of fibre impairments including chromatic dispersion, self-phase modulation, four wave mixing and stimulated Brillouin scattering. It is shown that how higher weights which are supposed to deliver higher quality are more affected by fibre impairments. At last, the experimental results of three users with different weights are demonstrated.